2021
DOI: 10.3389/fpls.2021.698585
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana eIF4E1 and eIF(iso)4E Participate in Cold Response and Promote Translation of Some Stress-Related mRNAs

Abstract: Plant defense and adaptation to adverse environmental conditions rely on gene expression control, such as mRNA transcription, processing, stability, and translation. Sudden temperature changes are common in the era of global warming; thus, understanding plant acclimation responses at the molecular level becomes imperative. mRNA translation initiation regulation has a pivotal role in achieving the synthesis of the appropriate battery of proteins needed to cope with temperature stress. In this study, we analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…eIF4E1 encodes a translation initiation factor 4E, which recognizes mRNA 5′‐cap structure and interacts with eIF4G and other factors to form the initiation complex, leading to translation initiation (Jackson et al ., 2010; Aitken & Lorsch, 2012). eIF4E1 has been reported to function in virus resistance, flowering time, root and root hair growth, and cold response (Robaglia & Caranta, 2006; Bastet et al ., 2018; Bastet et al ., 2019; Zhu et al ., 2020; Salazar‐Diaz et al ., 2021; T. Liu et al ., 2022). We found that eIF4E1 plays a crucial role in primary nitrate response and nitrate metabolism (Figs 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…eIF4E1 encodes a translation initiation factor 4E, which recognizes mRNA 5′‐cap structure and interacts with eIF4G and other factors to form the initiation complex, leading to translation initiation (Jackson et al ., 2010; Aitken & Lorsch, 2012). eIF4E1 has been reported to function in virus resistance, flowering time, root and root hair growth, and cold response (Robaglia & Caranta, 2006; Bastet et al ., 2018; Bastet et al ., 2019; Zhu et al ., 2020; Salazar‐Diaz et al ., 2021; T. Liu et al ., 2022). We found that eIF4E1 plays a crucial role in primary nitrate response and nitrate metabolism (Figs 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, double knockout of both eIF4E1 and eIF(iso)4E in Arabidopsis was lethal (Callot and Gallois, 2014). Arabidopsis eIF4E1 or eIF(iso)4E inactivation decreased tolerance to low temperatures (Salazar-Dıáz et al, 2021), while had no effect on elf18-induced resistance against the bacteria Pseudomonas syringae pv. maculicola (Wang et al, 2022).…”
Section: Bc-3 Desc Cyvmentioning
confidence: 98%
“…Cold-responsive translation initiation factors can also cause the translation of certain transcripts, preferentially under low temperature conditions to presumably contribute to cold acclimation; the identified transcripts included putative regulators of ICE (Salazar-Díaz et al, 2021).…”
Section: Ice Protein Activity Is Regulated In Different Waysmentioning
confidence: 99%
“…Interestingly, Singha et al (2014) reported that distinct codons were preferred for MPK KINASE KINASE (MPKKK) proteins in rice which they suggest might cause low expression under normal conditions and higher expression under stress conditions. Cold‐responsive translation initiation factors can also cause the translation of certain transcripts, preferentially under low temperature conditions to presumably contribute to cold acclimation; the identified transcripts included putative regulators of ICE (Salazar‐Díaz et al, 2021).…”
Section: Ice Protein Activity Is Regulated In Different Waysmentioning
confidence: 99%